2006
DOI: 10.1038/sj.mp.4001907
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of cognitive functions in chronic schizophrenic patients by recombinant human erythropoietin

Abstract: Schizophrenia is increasingly recognized as a neurodevelopmental disease with an additional degenerative component, comprising cognitive decline and loss of cortical gray matter. We hypothesized that a neuroprotective/neurotrophic add-on strategy, recombinant human erythropoietin (rhEPO) in addition to stable antipsychotic medication, may be able to improve cognitive function even in chronic schizophrenic patients. Therefore, we designed a doubleblind, placebo-controlled, randomized, multicenter, proof-of-prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
197
3
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(217 citation statements)
references
References 65 publications
8
197
3
6
Order By: Relevance
“…High-dose EPO (40,000 IU intravenously), applied over 12 weeks on a weekly basis, led to significant improvement of schizophrenia-relevant cognitive performance as compared to placebo-treated patients. 124 In addition to the stepwise improvement in cognitive performance, we found that EPO was able to delay progression of cortical gray matter loss in chronic schizophrenic patients, as determined by most comprehensive, voxel-based morphometrical MRI analysis (manuscript in preparation). In this respect, EPO-induced prevention of brain atrophy, as observed in rodent studies, 86 could be nicely reproduced in man.…”
Section: Schizophreniamentioning
confidence: 84%
See 2 more Smart Citations
“…High-dose EPO (40,000 IU intravenously), applied over 12 weeks on a weekly basis, led to significant improvement of schizophrenia-relevant cognitive performance as compared to placebo-treated patients. 124 In addition to the stepwise improvement in cognitive performance, we found that EPO was able to delay progression of cortical gray matter loss in chronic schizophrenic patients, as determined by most comprehensive, voxel-based morphometrical MRI analysis (manuscript in preparation). In this respect, EPO-induced prevention of brain atrophy, as observed in rodent studies, 86 could be nicely reproduced in man.…”
Section: Schizophreniamentioning
confidence: 84%
“…To our knowledge, no EPO variants other than rhEPO itself have thus far been published in relation to the treatment of human nervous system diseases. The only studies published so far reporting on efficacy of rhEPO in human brain diseases are our own studies on ischemic stroke, schizophrenia and MS. 69,119,124 …”
Section: Erythropoietin As Neuroprotective/ Neuroregenerative Treatmementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, sustained or increased brain BDNF by exogenous rhEPO co-treatment has the potential to prevent and/or reverse neuropathological events in schizophrenia (Glantz et al, 2006). In support of this possibility, a recent clinical add-on therapy, rhEPO with antipsychotic medication, showed significant improvement in cognitive function in chronic schizophrenia patients (Ehrenreich et al, 2007). In addition, rhEPO has therapeutic advantages over other neurotrophic factors in terms of delivery to their target cells in the brain and clinical tolerability (Abicht and Lochmuller, 1999;Horina et al, 1991).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, a recent study by Ehrenreich et al, 2007 has shown that rhEPO improves cognitive functions in chronic schizophrenic patients. We recently reported that HAL and olanzapine have distinct temporal effects on the expression of EPO and its receptor in adult rat brain .…”
Section: Introductionmentioning
confidence: 99%